A Virtual Fabrication and High-Performance Design of 65 nm Nanocrystal Floating-Gate Transistor - Thinh Dang Cong; Trang Hoang (Modelling and Simulation in Engineering)
Floating-gate transistor lies at the heart of many aspects of semiconductor applications such as neural networks, analog mixed-signal, neuromorphic computing, and especially in nonvolatile memories. The purpose of this paper was to design a high-performance nanocrystal floating-gate transistor in terms of a large memory window, low power, and extraordinary erasing speeds. Besides, the transistor achieves a thin thickness of the tunnel gate oxide layer. In order to obtain the high-performance design, this work proposed a set of structure parameters for the device such as the tunnel oxide layer thickness, Interpoly Dielectric (IPD), dot dimension, and dot spacing. Besides, this work was successful in the virtual fabrication process and methodology to fabricate and characterize the 65 nm nanocrystal floating-gate transistor. Regarding the results, while the fabrication process solves the limitation of the tunnel oxide layer thickness with the small value of 6 nm, the performance of the transistor has been significantly improved, such as 2.8 V of the memory window with the supply voltage of ±6 V at the control gate. In addition, the operation speeds are compatible, especially the rapid erasing speeds of 2.03 μs, 28.6 ns, and 1.6 ns when the low control gate voltages are ±9 V, ±12 V, and ±15 V, respectively.